Mutational analysis of ribosomal proteins in a cohort of pediatric patients with T-cell acute lymphoblastic leukemia reveals Q123R, a novel mutation in RPL10 - Bacci, Lorenza; Indio, Valentina; Rambaldelli, Guglielmo; Bugarin, Cristina; Magliocchetti, Franco; Del Rio, Alberto; Pollutri, Daniela; Melchionda, Fraia; Pession, Andrea; Lanciotti, Marina; Dufour, Carlo; Gaipa, Giuseppe; et al. (Frontiers in Genetics, 2022)
T-cell acute lymphoblastic leukemia (T-ALL) is a subtype of ALL involving the malignant expansion of T-cell progenitors. It is driven by a number of different possible genetic lesions, including mutations in genes encoding for ribosomal proteins (RPs). These are structural constituents of ribosomes, ubiquitous effectors of protein synthesis. Albeit the R98S mutation in RPL10, recurring with a higher frequency among RP mutations, has been extensively studied, less is known about the contribution of mutations occurring in other RPs. Alterations affecting translational machinery may not be well tolerated by cells, and there may be a selective pressure that determines the emergence of mutations with a compensatory effect. To explore this hypothesis, we sequenced the exomes of a cohort of 37 pediatric patients affected by T-ALL, and analyzed them to explore the co-occurrence of mutations in genes involved in ribosome biogenesis (including RPs) and translational control, and in known T-ALL driver genes. We found that some of the mutations in these sub-classes of genes tend to cluster together in different patients, indicating that their co-occurrence may confer some kind of advantage to leukemia cells. In addition, our sequencing highlighted the presence of a novel mutation in RPL10, namely the Q123R, which we found associated with a defect in protein synthesis. Our findings indicate that genetic alterations involving ribosome biogenesis and translational control should be carefully considered in the context of precision medicine in T-ALL.